The Role of Information Systems Audit in Preventing Data Processing Errors - Namira, Pasya; Wibisono, Fayakhun; Arifin, Aisyah Nurhaliza; Wardhani, Neng Sri (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Information systems are essential components in modern organizations, supporting operational activities, financial reporting, and strategic decision-making. However, weaknesses in system controls may lead to data processing errors that reduce data accuracy, reliability, and integrity. This study aims to comprehensively analyze the role of information systems audit in preventing data processing errors through the evaluation of internal controls, audit procedures, and information technology governance frameworks. This research employs a qualitative approach using a systematic literature review of international journals and conference proceedings published between 2015 and 2025. The results show that information systems audits play a critical preventive role by identifying risks at the input, processing, and output stages, as well as by strengthening internal control effectiveness. The implementation of continuous and risk-based information systems audits enhances data quality, minimizes processing errors, and supports effective IT governance. This study contributes theoretically and practically by presenting a structured audit framework that can be applied to improve data processing accuracy and organizational performance.